83.8k views
0 votes
2x - 5y + 3z = 27

4x + 3y - 7z=-37
x - 2y + 5z = 30
I need help solving this with cramers rule

User EoLithic
by
6.2k points

1 Answer

1 vote

Explanation: answer {x,y,z} = {1,-2,5}

/ Solve equation [3] for the variable x

[3] x = 2y - 5z + 30

// Plug this in for variable x in equation [1]

[1] 2•(2y-5z+30) - 5y + 3z = 27

[1] - y - 7z = -33

// Plug this in for variable x in equation [2]

[2] 4•(2y-5z+30) + 3y - 7z = -37

[2] 11y - 27z = -157

// Solve equation [1] for the variable y

[1] y = -7z + 33

// Plug this in for variable y in equation [2]

[2] 11•(-7z+33) - 27z = -157

[2] - 104z = -520

// Solve equation [2] for the variable z

[2] 104z = 520

[2] z = 5

// By now we know this much :

x = 2y-5z+30

y = -7z+33

z = 5

// Use the z value to solve for y

y = -7(5)+33 = -2

// Use the y and z values to solve for x

x = 2(-2)-5(5)+30 = 1

User Woodvi
by
6.0k points